SANKSI PIDANA TERHADAP WARGA NEGARA ASING PELAKU PENYALAHGUNAAN IZIN TINGGAL - Ramzy, Isvandiar Muhammad (Fakultas Ilmu Sosial dan Humaniora, 2023)
Abuse of residence permits is a legal incident that often occurs in immigration crimes. Residence permits for foreign nationals residing in Indonesian territory are often misused by these permit holders, resulting in many cases of abuse of residence permits. The method used is normative legal research or Legal Research. The results of the study are as follows: Perpetrators of abuse of residence permits are not subject to criminal sanctions under the immigration law, namely the handling of cases is shorter, namely through administrative actions in the form of deportation, and also considering the punishment. the law is